Plasma Treatment to Improve the Surface Properties of Recycled Post-Consumer PVC - Darbello Prestes, Sabrina Moretto [UNESP]; Mancini, Sandro Donnini [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Cruz, Nilson Cristino da [UNESP]; Schreiner, Wido Herwig; Rodolfo Junior, Antonio (Wiley-Blackwell, 2015)
Recycled post-consumer and virgin PVC were treated using SF6 radiofrequency plasmas of different powers (30-80 W) and exposure times (2-30 min). The treatment converted the hydrophilic PVC into hydrophobic. It was then determined the effect of the optimized treatment (2 min, 80W, 120 degrees) on the chemical composition, molecular structure, roughness, electrical resistivity and abrasion resistance. There was replacement of C, Cl and H atoms by F resulting in a structure that can no longer be characterized as PVC and explains the low surface wettability and its temporal stability. Upon the optimized treatment condition, it was possible to obtain recycled PVC with similar roughness and surface electrical resistivity but with higher contact angle and abrasion resistance than the untreated virgin material.
Keywords: Hydrophobicity; Plasma treatment; Poly(vinyl chloride) (PVC); Recycling; Surfaces